In-situ spectroelectrochemistry (UV-visible and infrared) of anodic films on iron in neutral phosphate solutions - Borrás, C. A. (2000)
The composition of anodic films on iron formed at different potentials in neutral solutions has been investigated by in-situ UV–vis and IR spectroscopies in the presence of PO4 3−, a non-contaminant inhibitor used in anticorrosive paints. Optical and electrochemical determinations were used to detect and characterize two well-defined current waves in the active region of Fe and a following passive zone at more positive potentials. The response has been associated with the presence on the surface, in the dissolution zone, of Fe3 II[PO4]2 as the main species and probably some [FeIIIPO4]. [FeIIIPO4] has been detected in the passive region by in-situ IR spectroscopy. Only minor amounts of Fe2+ and Fe3+ species in solution have been detected optically. These phosphated overlayers are believed to provide extra protective properties to the passivating film.